How do you simplify #m^4*2m^-3# and write it using only positive exponents?

1 Answer
Mar 8, 2017

Answer:

See the entire solution process below:

Explanation:

First, rewrite this expression as:

#2(m^4 * m^-3)#

Next, use this rule of exponents to consolidate the #m# terms:

#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#

#2(m^color(red)(4) * m^color(blue)(-3)) = 2m^(color(red)(4) + color(blue)(-3)) = 2m^1#

Now, we can use this rule for exponents to complete the simplification:

#a^color(red)(1) = a#

#2m^color(red)(1) = 2m#